Fighting organizational decline: a risk-based approach to organizational anti-aging. Issue 11 (27th August 2019) - Gotteiner, Sharon; Mas-Machuca, Marta; Marimon, Frederic
Abstract : Purpose: Most mature organizations face a major decline in performance at some time during their existence. For more than three decades, it has been suggested that the management practices that could cure a troubled company could have also kept it well. Inspired by this concept, this paper is proposing a preventive approach to early implementation of turnaround strategies as an alternative for otherwise traumatic rescue efforts, further along the downward spiral. Design/methodology/approach: Corporate turnaround strategies and associated risks are integrated with a risk-based approach, along with a proactive decision-making process. The link between turnaround research, resource-based view, the sources of organizational decline, and the governance of organizational-decline-related risks – is explained. Findings: The integrated model streamlines a preventive organizational process for considering the suitability of commonly used turnaround practices – for the non-crisis business routine of a mature company. By considering and adjusting the risks associated with such practices, it addresses risk aversion at the early stages of decline and determines the optimal sequence and timing of retrenchment and recovery activities. As such, it encourages mature companies to take actions for reducing their exposure to organizational decline. Accordingly, the model is named the "Anti-Aging" framework. Research limitations/implications: Empirical testing of the suitability of turnaround strategies for non-crisis situations is proposed as a direction for future research. Practical implications: The Anti-Aging framework opens an opportunity for the senior management of a mature organization to respond earlier to organizational decline and avoid the trauma associated with otherwise more challenging conditions, for the benefit of all stakeholders. Originality/value: The Anti-Aging framework proposes an innovative way of bridging the gap between the benefits of early implementation of turnaround strategies, and major obstacles faced by willing, traditional management teams of mature organizations.